Diagnosis and outcomes of pregnant women with Zika virus infection in two municipalities of Risaralda, Colombia: Second report of the ZIKERNCOL study. Issue 25 (September 2018) - Rodriguez-Morales, Alfonso J.; Cardona-Ospina, Jaime A.; Ramirez-Jaramillo, Valeria; Gaviria, Javier A.; González-Moreno, Gloria María; Castrillón-Spitia, Juan D.; López-Villegas, Alejandra; Morales-Jiménez, Estefania; Ramírez-Zapata, Valentina; Rueda-Merchán, German Eduardo; Trujillo, Adriana M.; Tabares-Villa, Fredy A.; et al.
Abstract: Background: Zika virus (ZIKV) infection has emerged as a significant threat for pregnant women and newborns in populations living in or visiting Latin America. We previously reported a preliminary analysis in Sucre, Colombia, as the first group of pregnant women with RT-PCR-confirmed ZIKV ( ZIK a en E mbarazadas y R ecién N acidos en COL ombia, ZIKERNCOL). Methods: In this second report, findings of the first 86 pregnant women from La Virginia and Dosquebradas (municipalities), Risaralda, Colombia, with RT-PCR-confirmed ZIKV infection are reported. Clinical, demographical and obstetrical findings are described. Results: All women reported ZIKV symptoms during pregnancy: 79.1% rash, 55.8% fever, among others. In addition to ZIKV, RT-PCR was positive for dengue in 18.6%; 45.3% Dengue IgM+; 5.8% RT-PCR positive for chikungunya; 3.6% Chikungunya IgM+. STORCH screening in mother: 11.6% IgG + anti- Toxoplasma gondii, 6% IgG + anti-rubella, 4.7% IgG + CMV. The rest of STORCH tests were negative. Microcephaly was observed in 2.4% of the newborns. No calcifications or other CNS alterations were detected. One newborn had cleft palate and one had bilateral renal ectopy. Conclusions: The rate of microcephaly in our cohort was consistent with other studies. Pregnant women in endemic areas should be followed and tested according to standard protocols, and asymptomatic ZIKV infection should be considered. Long-term follow-up of children is required in the congenital Zika syndrome (CZS) assessment.